2018
DOI: 10.1111/wrr.12625
|View full text |Cite
|
Sign up to set email alerts
|

Changes in PGE2 signaling after submandibulectomy alter post–tooth extraction socket healing

Abstract: Saliva is very important to oral health, and a salivary deficit has been shown to bring serious problems to oral health. There is scant information about the mechanisms through which salivary glands participate in post-tooth extraction socket healing. Therefore, the aim of the present study was to investigate the effect of submandibulectomy (SMx), consisting of the ablation of submandibular and sublingual glands (SMG and SLG, respectively), on PGE signaling and other bone regulatory molecules, such as OPG and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…15,39 Wound healing is a dynamic process. 2 We used the rat tooth extraction model to explore the relationship between ER stress and different bone healing stages. ER stress-related marker p-eIF2α/ eIF2α and osteogenic marker Runx2 expression was higher 14 days after tooth extraction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15,39 Wound healing is a dynamic process. 2 We used the rat tooth extraction model to explore the relationship between ER stress and different bone healing stages. ER stress-related marker p-eIF2α/ eIF2α and osteogenic marker Runx2 expression was higher 14 days after tooth extraction.…”
Section: Discussionmentioning
confidence: 99%
“…Wound healing is a dynamic process 2 . We used the rat tooth extraction model to explore the relationship between ER stress and different bone healing stages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Mohn et al demonstrated changes in biomechanical properties in mandibular bone of rats subjected to tooth extraction and submandibulectomy. 49 However, geometric and structural properties were not found to be altered herein either in non-treated EP rats or in those treated with Capz (data not shown), but were lowered in the group of EP rats receiving daily application of AM251 and AM630. Therefore, these results suggest that disruption of CB1r and CB2r pathways, through the performed intervention, leads to evident alterations in structural properties in maxillaries that could soften alveolar bone lessening its mineral content.…”
Section: Discussionmentioning
confidence: 87%
“…Recently, Mohn et al. demonstrated changes in biomechanical properties in mandibular bone of rats subjected to tooth extraction and submandibulectomy . However, geometric and structural properties were not found to be altered herein either in non‐treated EP rats or in those treated with Capz (data not shown), but were lowered in the group of EP rats receiving daily application of AM251 and AM630.…”
Section: Discussionmentioning
confidence: 92%